Psychological Essence and Motives of Prosocial Behavior of Personality - Derevyanko, Natalia (Psychological Prospects Journal, 2020)
The article analyzes the main theoretical approaches to understanding prosocial behavior. The author analyzes the theoretical and empirical researches of the problem and considers the main motives of prosocial action. The purpose of the article is to carry out a theoretical analysis of the essence and motives of prosocial behavior of the individual. Research Methods. The following theoretical methods of scientific research were used in the research: analysis, generalization, systematization of scientific literature on the study of prosocial behavior and motivation to perform prosocial actions. Results. Prosociality involves any kind of assistance for the benefit of another person or social community. It presupposes social interaction and characterizes the individual as a social slice capable of acting in the public interest. In psychological theory, there are several theories that explain what types of motives influence the commission of prosocial actions. These are the negative relief model, the cost-reward model, and the empathic-altruistic model. Conclusions. The main characteristic of prosocial behavior is its social adaptability, which is manifested in actions for the benefit of others. Prosocial behavior ensures the development of society, and is also an effective way to influence and manage the social masses. One of the most unresolved problems of prosocial behavior is the study of motives that motivate individuals to take helpful actions. The author identifies three groups of motives for prosocial behavior. The first group includes altruistic motives (the implementation of prosocial action for the benefit of others without benefit, the so-called «pure help»). The second group includes selfish motives, the motives that provide benefits for the helper. They can be internal motives: the motive of eliminating psychological discomfort, the motive of receiving positive emotions, the motive of self-encouragement and self-respect, etc.; and external motives, such as the motive of social recognition. The third group includes social motives, those that are generally accepted in society and in some way create a certain social pressure to carry out prosocial actions. These are religious and moral-ethical (mercy, patriotism) motives.